The impact of the use of e-Commerce on customer experience for retail in South Africa - Naidoo, Jaroshen (University of the Witwatersrand, Johannesburg, 2024)
e-Commerce systems are rapidly changing how individuals shop, and they have provided many retail stores in South Africa with a new sales channel to service customers. With many organisations heavily investing in e-Commerce systems, the need to have end users adopting e-Commerce is vital for the success of the future of e-Commerce. Two areas that need to be examined include how customers currently use e-commerce systems and how e-Commerce use impacts customer experience. To understand the challenges, factors influencing e-commerce usage and its impact on customer experience were investigated. This study distinguished between basic and advanced utilisation of e-commerce systems. To understand the research objectives identified, an extended version of the Delone and Mclean IS Success model has been adapted to the study, which has been modelled as an e-Commerce IS success model. The factors influencing the advanced use of e-Commerce systems include information, system, and service quality. With e-Commerce being split into basic and advanced use, advanced use was focused on understanding how it affects customer experience. This data was collected through a survey distributed to end users of e-Commerce over LinkedIn. 159 respondents(n=159) provided insights into the factors, which included Information quality, system quality, service quality, basic use, advanced use, user satisfaction, customer experience and data quality. However, data quality was a factor that dropped during the Structural Equation Modelling (SEM), which was done through SPSS and AMOS. The research showed strong relationships between information quality and advanced use, system quality and advanced use, and service quality and advanced use. This confirmed the first objective of understanding the factors that impact the advanced use of e-Commerce systems in retail in South Africa. The next major result showed that advanced use had a higher coefficient to the basic viii uses relationship towards customer experience, and this translated to end users wanting to make use of the advanced features of e-Commerce systems to make decision-making and Key Performance Indicators (KPI) easier to achieve. In the findings, numerous contributions have been made, which include the factors that impact the basic and advanced use of e-Commerce systems. The effects of the basic and advanced use on customer experience and user satisfaction, which did not previously exist within the e-Commerce space, are also contributions identified in this study. Overall, this study helps organisations understand what end users and customers would want to use when using e- Commerce platforms in terms of features and how customer experience can be influenced by new technologies and features introduced into the e-Commerce system for retail in South Africa.
A research report submitted in fulfillment of the requirements for the Master of Management in the field of Digital Business, In the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Customer experience; Delone and Mclean IS Success Model; e-Commerce systems; Electronic Commerce (E-Commerce); SDG-8: Decent work and economic growth; SDG-9: Industry, innovation and infrastructure